Innovative use of the fiberoptic bronchoscope - Mehta, Kaveri A; Ambulkar, Reshma P; Sharma, Kailash S; Chaukar, Devendra A (Indian Journal of Medical and Paediatric Oncology, 2012)
Tracheostomy can be challenging, especially in the presence of edema or infiltrative malignancy. We present a case in which a fiberoptic bronchoscope that is routinely used for difficult intubation helped to locate the trachea in an emergency situation. A 50 year-old male, a diagnosed case of anaplastic carcinoma of thyroid, presented with respiratory distress and was immediately taken to the operating theater for an emergency tracheostomy. Following an inhalational induction, the patient was intubated with an endotracheal tube. Surgical tracheostomy was extremely difficult as, on neck exploration, there was a plaque of disease infiltrating various tissue planes. When even after considerable dissection the trachea could not be located, we passed a fiberoptic bronchoscope through the endotracheal tube. This helped as it was seen as a trans- illumination and the tracheal position could be confirmed. The rest of the tracheostomy was uneventful.
Keywords: Anaplastic carcinoma of thyroid; difficult tracheostomy; fiberoptic bronchoscope